In vivo gastrointestinal drug-release monitoring through second near-infrared window fluorescent bioimaging with orally delivered microcarriers - Wang, Rui (Nat Commun, 2017)
Non-invasive monitoring of gastrointestinal drug release in vivo is extremely challenging because of the limited spatial resolution and long scanning time of existing bioimaging modalities, such as X-ray radiation and magnetic resonance. Here, we report a novel microcarrier that can retain drugs and withstand the harsh conditions of gastrointestinal tract. Significantly, we can track the microcarrier fate and semi-quantitatively monitor the content of drug released in vivo in real time by measuring the fluorescence signals in the second near-infrared window of lanthanide-based downconversion nanoparticles with an absorption competition-induced emission bioimaging system. The microcarriers show a prolonged residence time of up to 72 h in the gastrointestinal tract, releasing up to 62% of their content. Moreover, minimal deposition of the microcarriers is found in non-target organs, such as the liver, spleen and kidney. These findings provide novel insights for the development of therapeutic and bioimaging strategies of orally administered drugs.